Pengembangan Media Edukatif “Rumah Nusantara” pada Pembelajaran IPAS di Kelas V SD - Alisda Rasty Amellia Putri; Nabila Cahyaning Putri; Andin Anjelika Tiara Sasabila; Anggi Dwi Lestari; Dyandra Ramadhani; Rizqi Nararya Pangesti; Aini Nur Halimah (Prosiding Konferensi Ilmiah Dasar, 2026)
IPAS instruction in elementary schools still faces various challenges, one of which is the limited use of innovative and engaging instructional media, resulting in students tending to be less active and experiencing difficulty understanding the material. This study aims to develop the “Rumah Nusantara” instructional media for the IPAS subject in fifth grade elementary school and to describe the results of its implementation in the classroom. This study employed the Research and Development (RD) method with fifth-grade elementary school students as the research subjects. Data collection techniques included observation and documentation. The results indicate that the “Rumah Nusantara” learning medium is suitable for use in the classroom and received positive feedback from both teachers and students. The use of this learning medium was able to increase students’ engagement, interest, and understanding of the IPAS material, as well as create a more interactive and enjoyable learning atmosphere. Therefore, the “Rumah Nusantara” learning medium can be used as an alternative learning medium to support the IPAS learning process in elementary schools.